English grammar in use : A self-study reference and practice book for intermediate students. With answers - Murphy, Raymond (Cambridge : Cambridge University Press, 1990)
English grammar in use is a book for students of English who want to study and practise using the grammar of the language.
Keywords: English language; Grammar; English language -- Grammar -- Problems, exercises, etc